The Skin as a Window to Diabetes Mellitus: Manifestations, Complications and Clinical Insights - Kutaj, Aleksandra; Adamowicz, Zuzanna (Journal of Education, Health and Sport, 2025)
Introduction and purpose Diabetes mellitus (DM) is a chronic disease with a growing global prevalence, affecting 8.3% of adults, with a significant proportion remaining undiagnosed. The condition impacts multiple organ systems, including the skin, where manifestations often represent the earliest and most visible signs of metabolic dysregulation. Skin changes associated with DM, such as acanthosis nigricans, xerosis, diabetic dermopathy and necrobiosis lipoidica, not only highlight underlying metabolic disturbances but also provide valuable non-invasive tools for monitoring glycemic control and disease progression. Material and methods This study is based on a comprehensive review of recent literature focusing on the skin manifestations and clinical implications of diabetes mellitus -related skin changes. Description of the State of Knowledge Hyperglycemia disrupts normal cellular processes in the skin, leading to impaired wound healing, increased oxidative stress, and inflammation. These pathological changes contribute to various dermatological symptoms, including xerosis, pruritus, erythema, and fibrosis. Skin changes, such as diabetic dermopathy, necrobiosis lipoidica, and recurrent fungal infections, are not only indicators of DM but also reflect glycemic control and disease severity. These manifestations can signal undiagnosed diabetes or poorly controlled blood glucose levels, offering a non-invasive method for disease monitoring. Conclusions Skin manifestations are vital diagnostic tools in diabetes care, providing early indications of metabolic imbalances and poor glycemic control. Their presence underscores the need for timely interventions, including lifestyle modifications, pharmacological treatments, and patient education. Dermatological assessments, particularly in resource-limited settings, offer an accessible approach to monitoring therapy effectiveness and predicting complications.